Brill's Companion to Nonnus of Panopolis - Accorinti, Domenico (Brill's Companions in Classical Studies, 2016)
Contents -- Acknowledgements -- List of Abbreviations -- List of Illustrations -- List of Contributors -- Introduction: Becoming A Classic -- Part 1 Author, Context, and Religion -- Chapter 1 The Poet from Panopolis: An Obscure Biography and a Controversial Figure -- Chapter 2 Nonnus' Panopolis -- Chapter 3 The Religious Background of Nonnus -- Part 2 The Dionysiaca -- Chapter 4 Nonnus and Dionysiac-Orphic Religion -- Chapter 5 The Poet of Dionysus: Birth of the Last among the Gods -- Chapter 6 Major Themes and Motifs in the Dionysiaca -- Chapter 7 Minor Characters in the Dionysiaca -- Chapter 8 Narrative and Digression in the Dionysiaca -- Chapter 9 The Psychology in the Dionysiaca -- Part 3 The Paraphrase of St John's Gospel -- Chapter 10 Nonnus and Biblical Epic -- Chapter 11 Approaching the 'Spiritual Gospel': Nonnus as Interpreter of John -- Chapter 12 Nonnus' Paraphrastic Technique: A Case Study of Self-Recognition in John 9 -- Chapter 13 Nonnus and Christian Literature -- Chapter 14 Nonnus' Christology -- Chapter 15 The Mystery Terminology in Nonnus' Paraphrase -- Part 4 Metre, Style, Poetry, and Visual Arts -- Chapter 16 The Nonnian Hexameter -- Chapter 17 Nonnus' Conventional Formulaic Style -- Chapter 18 Nonnus and the Play of Genres -- Chapter 19 Nonnus' Poetics -- Chapter 20 Nonnus and the Poetry of Ekphrasis in the Dionysiaca -- Chapter 21 Nonnus and the Art of Late Antiquity -- Part 5 Nonnus and the Classical Tradition -- Chapter 22 Nonnus and the Homeric Poems -- Chapter 23 Composing the Masters: An Essay on Nonnus and Hellenistic Poetry -- Chapter 24 Nonnus and Imperial Greek Poetry -- Chapter 25 Nonnus and the Novel -- Part 6 An Interpretation of Nonnus' Work -- Chapter 26 Christian Themes in the Dionysiaca -- Chapter 27 Pagan Themes in the Paraphrase -- Chapter 28 Nonnus and Prophecy: Between 'Pagan' and 'Christian' Voices.